Modeling of a quasi-zero static stiffness mount fabricated with TPU materials using fractional derivative model. (1st September 2022) - Zheng, Yawei; Shangguan, Wen-Bin; Liu, Xiao-Ang
Highlights: A novel mount with QZSS and compact structure is proposed, fabricated and performances are measured. A model containing nonlinear elastic, friction, and viscous elements to characterize mounts behaviors is proposed and validated. Isolation at high frequencies is enhanced using fractional derivative damping. Abstract: Static behaviors of quasi-zero static stiffness (QZSS) mounts have been widely studied to isolate low frequency vibrations. However, Dynamic behaviors contributed by the damping of QZSS mounts are simplified as a linear viscous damping, leading to a misestimate of isolation performances at low frequencies. In this paper, dynamic behaviors of a novel QZSS mount are modeled and analyzed. Firstly, a mount with QZSS characteristic is designed using finite element method and then fabricated with Thermoplastic polyurethanes (TPU). Secondly, reacted forces of the fabricated mount under static, harmonic and random excitations are measured through the MTS device. Thirdly, a mechanical model consisting of nonlinear elastic, friction and fractional derivative force elements arranged in parallel is presented to capture the measured mount's nonlinear static, frequency-dependent and amplitude-dependent behaviors. Finally, a single degree of freedom system with a QZSS mount is used to investigate the influences of friction and fractional derivative models on the mount isolation performances.